Influence of 1, 5‐naphthalenediamine on thermomechanical properties of epoxy/copolyethersulphone blends. Issue 1 (31st August 2012) - Cicala, G.; Blanco, I.; Latteri, A.; Oliveri, L.; Recca, A.
Abstract The use of 1, 5‐naphthalenediamine (ND) as curing agents for epoxy blends was studied. The epoxy monomer was a standard diglycidyl ether of bisphenol A while as modifier a laboratory made copolyethersulphone (coPES) was considered. The coPES was added at three percentages: 10, 20, and 30% wt. The stiff structure of ND increased both viscosity and glass transition temperature of the blends. The blends cured by ND showed higher viscosity compared to resins cured by 3, 3′‐diammino diphenylsulfone or 4, 4′‐methylenebis(2, 6‐diethylaniline). Blends with higher coPES content (20 and 30% wt) showed viscosity fluctuation suggesting phase separation initiation but the combination of high viscosity and reactivity hindered the demixing process. This effect resulted in single glass transition for all formulations confirming the absence of phase separation. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers